Structural Violations of Mental Health Equity among Divorced Women: Challenges and Policy Implications - Fathima Sherin Ottakkam Thodukayil; Rahana Salahudeen Raseena; Udhayakumar Palaniswamy; Sigamani Panneer; Sainaba Parammal (Social Work and Society, 2024)
The mental health equity of divorced women is a critical concern, as divorce can have significant emotional and psychological implications. Mental health equity refers to ensuring all individuals have equal access to mental health resources, support, and care regardless of their circumstances. Even though there are disparities in mental health care affecting mental health equity especially among divorced women, there is a noticeable gap in studies that delve into this issue. In this context, employing a mixed-method approach, this study explored the prevalence of mental health issues in divorced women and identified structural violations contributing to disparities in mental health care. The sample encompassed of divorced women in Kerala, representing diverse socio economic backgrounds, who were selected through purposive sampling. The data for the quantitative analysis was collected from 60 respondents in Kerala using the Depression, Anxiety, and Stress Scale (DASS21) to assess the mental health status of the women and a demographic questionnaire. In-depth face-to-face interviews with seven women were conducted for qualitative analysis. The findings of the study showed that the women experience significant mental health impairments in their post-divorce phase, and highlighted the impact of pre-existing structural violations and intersections of gender, class, and marital status of women in hindering their access to mental health care. Urgent policy interventions are needed to address these issues and cater to the specific needs of marginalized groups, especially, divorced women.